2016 IEEE 19th International Conference on Intelligent Transportation Systems (ITSC) 2016
DOI: 10.1109/itsc.2016.7795658
|View full text |Cite
|
Sign up to set email alerts
|

Drowsiness in Conditional Automation: Proneness, diagnosis and driving performance effects

Abstract: Abstract-Fatigue and drowsiness can play an important role in Conditional Automation (CA), as drowsy drivers may fail to properly recover control.In order to provide better insight in the effects of drowsy driving in Take Over Request (TOR), we designed a driving experiment that extends related literature in drowsiness research CA with self-rated subjective drowsiness, and analyze TOR performance adopting methods from recent TOR publications.Results show that under certain conditions, drivers are very prone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…They further noted that both fatigued and drowsy drivers with automation were biased toward choosing to brake rather than steer in response to a takeover request due to a rear-end emergency. Finally, Gonçalves et al (2016) found that subjectively drowsy drivers had higher maximum posttakeover lateral acceleration, although they observed no impacts on longitudinal control or takeover time. The preliminary findings suggest that driver task-related fatigue and drowsiness are relevant modeling components for steering and braking decisions and visual reaction time; however, findings are inconclusive, and significant future work is needed.…”
Section: Review Of Automated Vehicle Takeoversmentioning
confidence: 89%
See 2 more Smart Citations
“…They further noted that both fatigued and drowsy drivers with automation were biased toward choosing to brake rather than steer in response to a takeover request due to a rear-end emergency. Finally, Gonçalves et al (2016) found that subjectively drowsy drivers had higher maximum posttakeover lateral acceleration, although they observed no impacts on longitudinal control or takeover time. The preliminary findings suggest that driver task-related fatigue and drowsiness are relevant modeling components for steering and braking decisions and visual reaction time; however, findings are inconclusive, and significant future work is needed.…”
Section: Review Of Automated Vehicle Takeoversmentioning
confidence: 89%
“…Takeover time budgets also significantly impact the driver's choice of posttakeover response (i.e., braking, steering, or a combination), with braking becoming more common at lower time budgets Gold et al, 2017). This trend in decision making is also aligned Feldhütter, Gold, Schneider, and Bengler (2017); Gold, Berisha, and Bengler (2015); ; ; Gold, Körber, Lechner, and Bengler (2016); Gonçalves, Happee, and Bengler (2016); Kerschbaum, Lorenz, and Bengler (2015); Körber, Baseler, and Bengler (2018); Körber, Gold, Lechner, Bengler, and Koerber (2016); Kreuzmair, Gold, and Meyer (2017) with manual driving (Lee, Llaneras, Klauer, & Sudweeks, 2007). Summary of takeover time budget effects.…”
Section: Takeover Time Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative impact of automated driving, mainly linked to fatigue appears to increase with time spent under automation [4, 15, 18–20]. A previous study found that drivers rated themselves as subjectively tired even after only 15 min of automated driving [21]. Objective measures of driver fatigue also confirmed the impairment of cognitive state during 20 [22] or 42 min of automated driving [23].…”
Section: Introductionmentioning
confidence: 95%
“…Specifically, two studies used a combination of visual and auditory signals, and the other 2 studies used single auditory alerts. The lead times (i.e., time budget) between takeover events and takeover requests ranged from 5 to 7 seconds (Feldhutter et al, 2018(Feldhutter et al, , 2019Gonçalves et al, 2016;Jarosch et al, 2019).…”
Section: Takeover Measuresmentioning
confidence: 99%